Enhancement of oral bioavailability of ibrutinib using a liposil nanohybrid delivery system. - Fareeaa Ashar; Asif Ansari Shaik Mohammed; S Selvamuthukumar (PLoS ONE)
Liposils, synthesized via the liposome templating method, offer a promising strategy for enhancing liposome stability by employing a silica coating. This study focuses on the development of nanocarriers utilizing silica-coated nanoliposomes for encapsulating the poorly water-soluble drug, ibrutinib. Ibrutinib-loaded nanoliposomes were meticulously formulated using the reverse-phase evaporation technique, serving as templates for silica coating, resulting in spherical liposils with an average size of approximately 240 nanometers. Comprehensive characterization of the liposil's physical and chemical properties was conducted using various analytical methods, including dynamic light scattering, transmission electron microscopy, Fourier-transform infrared spectroscopy, and X-ray diffraction analysis. Liposils demonstrated superior performance compared to ibrutinib-loaded nanoliposomes, showing sustained drug release profiles in simulated intestinal fluids and resistance to simulated gastric fluid, as confirmed by dissolution studies. Moreover, ibrutinib liposils exhibited a significant increase in half-life (4.08-fold) and notable improvement in bioavailability (3.12-fold) compared to ibrutinib suspensions, as determined by pharmacokinetic studies in rats. These findings underscore the potential of liposils as nanocarriers for orally delivering poorly water-soluble drugs, offering enhanced stability and controlled release profiles, thereby improving bioavailability prospects and therapeutic efficacy. This approach holds promise for addressing challenges associated with the oral administration of drugs with limited solubility, thereby advancing drug delivery technologies and clinical outcomes in pharmaceutical research and development.